Stellate Ganglion Block for Psychiatric Disorders: A Systematic Review of the Clinical Research Landscape. (December 2021) - Kerzner, Jaimie; Liu, Helen; Demchenko, Ilya; Sussman, David; Wijeysundera, Duminda N.; Kennedy, Sidney H.; Ladha, Karim S.; Bhat, Venkat
Stellate ganglion block (SGB) is a procedure involving the injection of a local anesthetic surrounding the stellate ganglion to inhibit sympathetic outflow. The objective of this review was to summarize existing evidence on the use of SGB in adults with psychiatric disorders. A systematic search identified 17 published studies and 4 registered clinical trials. Eighty-eight percent of published studies, including 2 randomized controlled trials (RCTs), used SGB for posttraumatic stress disorder (PTSD), although its use for schizophrenia spectrum disorders was also explored. Administration of 1 to 2 SGBs using right-sided laterality with 0.5% ropivacaine was most common. Preliminary evidence from clinical trials and case studies supports the feasibility of SGB for treating psychiatric disorders involving dysregulation of the sympathetic nervous system, although effectiveness evidence from RCTs is mixed. One RCT concluded that improvement in PTSD symptoms was significant, while the other concluded that it was nonsignificant. Improvements were noted within 5 minutes of SGB and lasted 1 month or longer. Registered clinical trials are exploring the use of SGB in new psychiatric disorders, including major depressive disorder and borderline personality disorder. More studies with larger sample sizes and alternate protocols are needed to further explore therapeutic potential of SGB for psychiatric disorders.